Risk factors and long-term outcomes in anterior iliac and obturator hip dislocation - Jaecker, Vera; Regenbogen, Stephan; Märdian, Sven; Brinkema, Hanno; Stöckle, Ulrich; Shafizadeh, Sven (European journal of trauma and emergency surgery, 2025)
Purpose Traumatic anterior hip dislocation is a severe but poorly studied injury. This study aimed to analyze characteristics, risk factors and prognostic factors regarding long-term morbidity and outcomes in patients who had sustained traumatic anterior hip dislocation. Methods Demographics, injury mechanism, and treatment-related characteristics of patients with anterior hip dislocations at three level-one trauma centers from 2009–2023 were analyzed. Acetabular and femoral morphology were assessed using CT scans to identify anatomical risk factors. Incidence of avascular necrosis (AVN), post-traumatic osteoarthritis (PTOA), further complications, return to work and sports, and patient-reported outcomes (PROMs), including Tegner Activity Scale (TAS) and modified Harris Hip Score (mHHS) were recorded at the follow-up. Results Out of 196 patients with traumatic hip dislocations, 19 anterior dislocations (12 iliac anterosuperior and 7 obturator) were identified. Ipsilateral knee injuries occurred in 36.8%, and 73.7% had concomitant femoral head or acetabular rim fractures. Obturator dislocations were commonly simple dislocations, while iliac dislocations involved more complex associated fractures often requiring surgery. Acetabular anteversion and cam-type femoroacetabular impingement (FAI) were identified as risk factors. Twelve patients (63%) were available for follow-up (mean 8.33 ± 5.05 years). The majority demonstrated good to excellent mHHS (mean 86.9), and minimal TAS decrease (5.33 to 4.67). AVN was not observed, and only one patient required hip arthroplasty following PTOA. Conclusion Anterior hip dislocations commonly result from high-energy “dashboard" injuries, with acetabular anteversion and cam-type FAI morphology being contributing risk factors. Long-term functional outcomes were favorable, with low rates of avascular necrosis or osteoarthritis, independent of type and complexity of the dislocation.
Gesehen am 29.10.2025